New variety, records & discoveries of some species of Pandanus (Pandanaceae) in Sumatra & Kalimantan, Indonesia - Keim, Ary Prihardhyanto (REINWARDTIA, 2012)
This current study shows the presence of a new variety of Pandanus korthalsii Solms from Bengkulu, P. korthalsii Solms var. bengkuluensis A.P. Keim and records the presence of three species from Pandanus previously unknown to Sumatra and Borneo, particularly Kalimantan: Pandanus irregularis Ridl., P. labyrinthicus Kurz, and P. stelliger Ridl. The result of this study also indicates that in Sumatra the coastal-inhabitant P. labyrinthicus can also be found further inland from its previously known habitat.